DETERMINING INTERESTS AND TALENTS OF PRIMARY SCHOOL STU-DENTS USING THE CERTAINTY FACTORS - Lubis, Mustopa Husein; Martina, Desy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: Interest is an interest in an object that comes from the heart. Talent is a condition in a person that enables him with special training to achieve a special skill, knowledge, skill. For this reason, an expert system for determining students' interests and talents was designed. The method used in this research is the certainty factor (CF) method. The results based on the characteristics experienced by these students show that the type of interest and talent that exists in these students is linguistics with an expertise level of 0.66 and a percentage of 66% and has a fairly good accuracy score. Keywords: certainty factor;interest; talent Abstrak: Minat merupakan ketertarikan akan sesuatu objek yang berasal dari hati. Bakat adalah suatu kondisi pada seseorang yang memungkinkannya dengan suatu latihan khusus mencapai suatu kecakapan, pengetahuan, keterampilan khusus Untuk itu dirancang suatu sistem pakar penentuan minat dan bakat siswa. Metode yang digunakan pada penelitian kali ini ialah metode faktor kepastian (CF),. Hasil bedasarkan ciri-ciri yang dialami oleh siswa tersebut bahwa jenis minat dan bakat yang ada pada siswa tersebut adalah linguistik dengan tingkat kepakaran 0,66 dan persentase 66 % dan memiliki nilai akuasi yang cukup baik. Kata kunci: bakat ; faktor kepastian;minat